Rabies Encephalitis: Fatal Yet Neglected, A Case Report - F. A. Simarmata, Junius; Ritarwan, Kiking (Journal of Society Medicine, 2024)
Introduction: Rabies is a zoonotic disease that can attack the central nervous system and can be fatal because it can cause death. Rabies is caused by an RNA virus of the genus Lyssavirus in the family Rhabdoviridae and can be transmitted to humans through contact with infected animals, particularly bites and scratches. Most cases (98%) were caused by dog   bites and the rest by other animals such as monkeys and cats. This disease has a very poor prognosis, but can be prevented by vaccination. Rabies virus is a neurotrophic virus that can infect humans and cause fatal encephalitis. Method: This was a retrospective case report, after analysis of patient clinical data. The patient’s family  provided written  informed  consent  to  publish  their  case  details  and  any accompanying images. Results: A 73-year-old man has clinical encephalitis with suspected viral EC with suspected rabies dd/non-specific viral dd bacterial. Patients complain of not being able to swallow and afraid  of water, restlessness, hypersalivation, patients are sensitive to  sound,  shortness  of  breath, difficulty  swallowing, fear  of  wind,  patients  want  to  bite  and  hydrophobia,  aerophobia  and hypersalivation. Conclusion: Rabies eradication is necessary because Indonesians are culturally close to animals, especially dogs, which are the main transmitters of rabies. In some areas, dogs are pets that are very close to their owners. Rabies is a neglected tropical disease. Most cases of rabies occur in Asia and Africa. There is no effective treatment to cure rabies but the disease can be prevented by handling rabies bite cases (GHPR) as early as possible.